UNDER/OVER HARGA PASAR SAHAM BBNI TERHADAP NILAI PERUSAHAAN - Simorangkir, Panubut (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2015)
This study was conducted to determine whether the company's performance BBNI reflected in the market price of its shares. An assessment of the share price calculated by the method BBNI Discounted Earnings Approach. The approach used is the analysis of top-down where the approach begins with a macroeconomic analysis, industry analysis and then proceed with the analysis of the company, analysis of financial projections for the next few years and then analyzes the determination of the intrinsic value of the company with a variety of basic assumptions gained through the process of collecting the data secondary. Based on the results of the calculation of the valuation by Discounted Earnings Approach at the end of 2014 should BBNI stock price of Rp 6.653, while in reality the closing price at the end of 2014 amounted to Rp 6.100, which means that the undervalued share price. Price estimasian of valuation calculations with Discounted Earnings Approach indicates that BBNI share intrinsic value at the end of 2015 should be in the range of Rp. 8.654